Monitoring the quality of training using multi-agent systems - Khavina, I. P. (ISMA University of Applied Science, 2021)
The use of artificial intelligence in learning has spawned a new direction in intelligent training systems. At the same time, the creation of effective innovative technologies for teaching and self-education is possible in the case of revision, rethinking and reevaluation of basic didactic categories and concepts on a trans-disciplinary basis, while maintaining the cultural and historical continuity of pedagogical knowledge. The paper presents the concept of an intelligent training system based on intelligent agents. A feature of the system is the use of a system for monitoring the quality of education in order to predict success and assess the level of competencies, and form an individual approach.
Keywords: intelligent training systems; intelligent agent; predict success; individual approach